2012
DOI: 10.1007/s10549-012-2297-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of follow-up care and early relapse detection in breast cancer patients

Abstract: Routine breast cancer follow-up aims at detecting second primary breast cancers and loco regional recurrences preclinically. We studied breast cancer follow-up practice and mode of relapse detection during the first 5 years of follow-up to determine the efficiency of the follow-up schedule. The Netherlands Cancer Registry provided data of 6,509 women, operated for invasive non-metastatic breast cancer in 2003-2004. In a random sample including 144 patients, adherence to follow-up guideline recommendations was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 23 publications
5
36
2
Order By: Relevance
“…We can consider our patients were regularly monitored, as there was only 13.2% missing mammographies during the first 5 years. Previous studies reported 8.7%‐28% missing mammographies during the first year and 29%‐40.7% during the second year . The time between the last mammography and the recurrence was 12.3 months (1.2 months to 5.1 years) in our study, compared to 16.4 months reported by Paszat et al .…”
Section: Discussioncontrasting
confidence: 57%
“…We can consider our patients were regularly monitored, as there was only 13.2% missing mammographies during the first 5 years. Previous studies reported 8.7%‐28% missing mammographies during the first year and 29%‐40.7% during the second year . The time between the last mammography and the recurrence was 12.3 months (1.2 months to 5.1 years) in our study, compared to 16.4 months reported by Paszat et al .…”
Section: Discussioncontrasting
confidence: 57%
“…The studies focusing on follow-up care in BCSs have been conducted in different populations worldwide, most of them in the US (n=19),27,3336,4143,46,5359,6365 followed by the UK (n=10),26,31,32,39,40,45,51,52,61,62 and the Netherlands (n=7) 23,24,38,44,48,49,60…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 summarizes six studies assessing the effectiveness of follow-up care in BCSs, where each study evaluated a different outcome including mortality, detection of recurrence, increase in surveillance testing, and reduction in anxiety 6065. For example, the results of two studies showed that surveillance mammography was effective in reducing breast cancer mortality 63.…”
Section: Resultsmentioning
confidence: 99%
“…Such practices result in a disproportionate number of overdiagnoses (FPs). Similarly, advanced technologies may have limited value for routine follow-up examinations of cancer patients [23,24].…”
Section: Clinical Practice and Theoretical Considerationsmentioning
confidence: 99%